A comparison of the efficacies between E20 dental waterline treatment and a homemade cost-effective 2% hydrogen peroxide solution as dental unit waterline disinfectants in the UP College of Dentistry Clinics - Algarne, Wilgem O.; Bermejo, Marco Emmanuel; Lim, Kerwin P. (Department of Community Dentistry, University of the Philippines Manila, 2022)
INTRODUCTION:The dental unit waterline (DUWL) is a source of infection in dental clinics that must be controlled by chemical or non-chemical means. Multiple studies have proven that hydrogen peroxide disinfectants lower bacterial counts in DUWLs.